Medpoklicno nasilje v operativni dejavnosti - Oblak, Tina (Obzornik zdravstvene nege, 2018)
Introduction: Perioperative care is generally delivered by a heterogeneous group of professionals with different personalities and value systems who share the responsibility for one patient, which may trigger tension in relationships and even escalate into violence. The aim of the study was to show how often this phenomenon occurs and to specify the related factors and consequences. Methods: A systematic search strategy in CINAHL, Medline, Academic Search Elite, ProQuest and COBIB. SI databases was implemented. We considered publications with the date of publication from January 2008 to December 2017. We used the following search key words in the English language: aggressive behavior, disruptive behavior, operating room, perioperative, violence, verbal abuse, bullying, surgeon and in Slovenian nursing care (zdravstvena nega), violence (nasilje). There were 735 results. Based on the title and abstract 68 of them matched the determinants, while 47 were removed after reviewing the content. Results: The conclusions of the literature review were based on 22 references. 6 categories were formed: (1) agents and levels of violence, (2) type of violence, (3) direct causes of violence in the operating theater, (4) factors related to the occurrence and identification of violence, (5) consequences of violence and (6) individual and systemic organizational measures for managing the consequences of violence. Discussion and conclusion: The most common agents of violence in perioperative care are surgeons and perioperative nurses, while the most common causes include hierarchy, unpredictable situations, lack of staff and material, interpersonal relations, workload, and organizational culture. The need for such representative research in Slovenia has been identified.
Keywords: disruptive behavior; interprofessional relationship; medpoklicni odnos; moteče vedenje; occupational health; organizacijska kultura; organizational culture; verbal aggression; verbalna agresija; zdravje pri delu